Service Quality and Promotion Impact on Purchasing Decisions and Consumer Satisfaction in Using Aqua Bottled Water by PT Tirta Investama in Gebang Purworejo District - Lestari, Tri Wahyu; Nurjaya, Nurjaya; Merdiani, Wentri; Nova Putra, Aditya; Rizky, Nur Ainiyah Dini (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
This research aims to determine the influence of service quality and promotion on purchasing decisions which have an impact on consumer satisfaction in using Aqua bottled water produced by PT Tirta Investama in the Gebang Purworejo District Area. The method used is explanatory research with a sample of 96 respondents. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this research are that service quality has a significant positive effect on purchasing decisions by 29.1%, the hypothesis test shows a significance of 0.000 <0.05. Promotion has a significant positive effect on purchasing decisions by 46.2%, hypothesis testing obtained a significance of 0.000 < 0.05. Service quality and promotion simultaneously have a significant positive effect on purchasing decisions by 49.6%, the hypothesis test obtained a significance of 0.000 <0.05. Purchasing decisions have a significant positive effect on consumer satisfaction of 30.1%, hypothesis testing obtained a significance of 0.000 <0.05.